Internalisasi Nilai-Nilai Agama Islam dalam Membentuk Karakter Siswa di SD Negeri Inpres 2 Koya Barat - Hajrah, Siti; Zulihi, Zulihi; Taslim, Taslim (CV. Creative Tugu Pena, 2024)
Education in Indonesia in the last decade has many problems, one of which is the loss of morality or character that marks the young generation and this is an important discussion that should be considered by all of us. As well as many students who show poor character such as promiscuity or others.... Therefore, researchers focus on the internalisation of Islamic religious values in shaping the character of students at SDN inpres 2 koya barat. This research aims to 1). Knowing the form of internalisation of Islamic religious values in shaping the character of students at SDN inpres 2 koya barat. 2). Knowing the supporting and inhibiting factors for the internalisation of Islamic religious values in shaping the religious character of students at SDN inpres 2 koya barat In this study using qualitative research. The approach method used is the Interdisciplinary approach. Data collection methods researchers use interview, observation and documentation methods. The data processing and analysis methods are data reduction, data presentation and conclusion drawing. The form of internalisation of Islamic religious values in shaping the character of participants is the value of religious character, nationalism, mutual cooperation, and integrity. The supporting factors for the internalisation of Islamic religious values in shaping the religious character of students at SDN inpres 2 Koya Barat are teacher workhsop, cohesiveness between committee administrators, and comfortable school conditions. The inhibiting factors for the internalisation of Islamic religious values in shaping the religious character of students at SDN inpres 2 Koya Barat are environmental factors, peers, and lack of self-awareness of the importance of character education. Keywords: Islamic Religious Values, Internalization Education Character